Reflections on the data collection process of a study with rural school communities in Rio Grande do Sul - Morgana Pappen; Ana Carolina Bienert; Betina Franciele Schwinn; Camila Becker; Luci Helen Alvez Freitas; Vitória Gelsdorf Dumke; Hildegard Hedwig Pohl; Suzane Beatriz Frantz Krug (Revista Brasileira de Educação do Campo, 2024)
Research in rural areas is essential to understand the necessary demands of the population, in addition to enabling the development of effective strategies according to the disparities and characteristics of this environment. The article aims to describe and reflect on weaknesses and potential elements in the data collection process of a study with school communities in rural areas of RS. This is an experience report, originating from data collection for doctoral research. The participants were students, parents, education and health professionals, municipal secretary of education and health. Data collection was the application of questionnaires and recording of interviews and data analysis was through content analysis, in addition to being approved by the research ethics committee. As positive aspects, the receptivity of the municipalities, adherence to research and mobilization of municipal management stand out. As negative aspects, it was considered the difficult access to the rural area, difficulty in reconciling schedules, frequent change of municipal secretaries and difficulty in contacting the Regional Health Coordinators. It is concluded that research in the rural community is vital to understand the needs of the population and regional culture.